2004
DOI: 10.1007/s11176-005-0050-3
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoro-1-(butylimino)butyl isothiocyanate. Synthesis and reaction with n-propylamine

Abstract: The reaction of perfluoro-5-azanon-4-ene with KSCN in an aprotic dipolar solvent provides perfluoro-1-(butylimino)butyl isothiocyanate. The latter was reacted with n-propylamine in the presence of triethylamine to obtain fluoro-substituted derivatives of thiourea, heptafluoropropionic acid, and 1,3,5-thiadiazine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Perfluorinated isothiocyanates 25 [29][30][31] and 26 [32] readily prepared by the reaction of perfluoro(2-methyl)pentene-2 [33,34] or perfluoro-4-aza-nonene-3 [35,36] with sodium thiocyanate were used for the synthesis of a variety of fluorinated heterocycles (see Refs. [37][38][39][40][41][42][43][44][45][46][47][48] and [32] for reactions of 25 for 26, respectively).…”
Section: Reactions Of Epoxides 1 and 2 With Aryl- Fluoroalkenylisothmentioning
confidence: 99%
See 1 more Smart Citation
“…Perfluorinated isothiocyanates 25 [29][30][31] and 26 [32] readily prepared by the reaction of perfluoro(2-methyl)pentene-2 [33,34] or perfluoro-4-aza-nonene-3 [35,36] with sodium thiocyanate were used for the synthesis of a variety of fluorinated heterocycles (see Refs. [37][38][39][40][41][42][43][44][45][46][47][48] and [32] for reactions of 25 for 26, respectively).…”
Section: Reactions Of Epoxides 1 and 2 With Aryl- Fluoroalkenylisothmentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44][45][46][47][48] and [32] for reactions of 25 for 26, respectively). In this study it was shown that both 25 and 26 (generated in situ by reaction with KSCN in DMF, Scheme 17) rapidly react with 2 giving of the corresponding cyclic imines 25a and 26a, respectively.…”
Section: Reactions Of Epoxides 1 and 2 With Aryl- Fluoroalkenylisothmentioning
confidence: 99%